Imaginaire des îles de l’Extrême-Nord dans la littérature géographique de la Renaissance : confusions et transferts - Mund-Dopchie, Monique (Presses universitaires de Rennes, 2019)
The emergence of an almost uniform representation of the northern-most islands can essentially be explained by two thought processes of the imagination: confusion and transfer of facts. Onomastic confusion stems from the first thought process and this confusion sometimes makes one write on the map as many places as there are onomastic variables–the variant spelling of Groenland/Grocland. Moreover, sometimes the characteristics of places are mixed-up, the names of which are semantically (Islandia/Frislandia) or phonetically (Ireland/Iceland) close. On top of these linguistic confusions can be added chronological confusions, as the authors of maps and textual descriptions confuse information relating to a different period of history of the island concerned. A third type of confusion stems from the usual method of accumulating data for encyclopaedias, when new data is regularly added to topics that have already been written without revising the entire entry; hence the feeling of vagueness that comes across when reading some of them. As for the transference of data, it is made either from one island to another (horizontal transfer), or from one period of history to another (vertical transfer). One example of horizontal transferences is the Icelandic appropriation of maps and topics devoted to Greenland, particularly the (hypothetical) existence of the Convent of Saint-Thomas in Greenland, which seems to have been superimposed on the monastery in Helgafell that really did exist. As for vertical transfers, we can note the importance of a tradition in antiquity which relates to the Northern barbarians and that of medieval discourse about the evangelisation of the northern islands in order to judge the degree of civilisation reached by the different islanders. Confusion and transfer therefore contribute to the integration of the northern islands into a powerful image already set in motion during antiquity: that of a wonderful place at the end of the world, where the inhabitants continue to maintain the way of life of ...